Development of a novel ultrasensitive enzyme immunoassay for human glutamic acid decarboxylase 65 antibody. (July 2016) - Numata, Satoshi; Katakami, Hideki; Inoue, Shinobu; Sawada, Hirotake; Hashida, Seiichi
Background: We developed a novel, ultrasensitive enzyme immunoassay (immune complex transfer enzyme immunoassay) for determination of glutamic acid decarboxylase autoantibody concentrations in serum samples from patients with type 2 diabetes. Methods: We developed an immune complex transfer enzyme immunoassay for glutamic acid decarboxylase autoantibody and measured glutamic acid decarboxylase autoantibody from 22 patients with type 1 diabetes, 29 patients with type 2 diabetes, and 32 healthy controls. Results: A conventional ELISA kit identified 10 patients with type 1 diabetes and one patient with type 2 diabetes as glutamic acid decarboxylase autoantibody positive, whereas 15 patients with type 1 diabetes and six patients with type 2 diabetes were identified as glutamic acid decarboxylase autoantibody positive using immune complex transfer enzyme immunoassay. Conclusions: Immune complex transfer enzyme immunoassay is a highly sensitive and specific assay for glutamic acid decarboxylase autoantibody and might be clinically useful for diabetic onset prediction and early diagnosis.